Soil Erosion as A Function of Natural And Anthropogenic Factors and Its Environmental Consequences. - Aliyev, prof.RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
The article examines the issues of the possibility of studying erosion and its control. The study proved that the development of soil erosion is based on the forming impact of natural and anthropogenic factors. The degree of potential danger and the possibility of prevention, taking into account the preservation of the environmental situation in the foothills of the Upper Shirvan in the example of the Shamakhi district of the Republic of Azerbaijan, were studied. The main tasks of the study were the determination of the amount and the degree of development of eroded and erosion-prone soils of the foothill zones, carried out on the basis of soil.